SCAPS-1D Simulation for Device Optimization to Improve Efficiency in Lead-Free CsSnI3 Perovskite Solar Cells - Hyun-Jae Park; Hyojung Son; Byoung-Seong Jeong (Inorganics, 2024)
In this study, a novel systematic analysis was conducted to explore the impact of various parameters, including acceptor density (NA), individual layer thickness, defect density, interface defect density, and the metal electrode work function, on efficiency within the FTO/ZnO/CsSnI3/NiOx/Au perovskite solar cell structure through the SCAPS-1D (Solar Cell Capacitance Simulator in 1 Dimension) simulation. ZnO served as the electron transport layer (ETL), CsSnI3 as the perovskite absorption layer (PAL), and NiOx as the hole transport layer (HTL), all contributing to the optimization of device performance. To achieve the optimal power conversion efficiency (PCE), we determined the ideal PAL acceptor density (NA) to be 2 × 1019 cm−3 and the optimal thicknesses to be 20 nm for the ETL (ZnO), 700 nm for the PAL (CsSnI3), and 10 nm for the HTL (NiOx), with the metal electrode remaining as Au. As a result of the optimization process, efficiency increased from 11.89% to 23.84%. These results are expected to contribute to the performance enhancement of eco-friendly, lead-free inorganic hybrid solar cells with Sn-based perovskite as the PAL.